Cultural identity, clothing and common mental disorder: a prospective school-based study of white British and Bangladeshi adolescents. Issue 5 (15th April 2008) - Bhui, K; Khatib, Y; Viner, R; Klineberg, E; Clark, C; Head, J; Stansfeld, S
Abstract : Objective: Cultural integration is the healthiest outcome for young people living in multicultural societies. This paper investigates the influence of different cultural identities on the risk of common mental disorders among Bangladeshi and white British pupils. Design: The cultural identity of 11–14-year-old school pupils was assessed by their preferences for friends and clothes of their own or other cultural groups; using this information pupils were classified into traditional, integrated, assimilated or marginalised groups. We undertook prospective analyses of cultural identity and its impacts on the later mental health of young people. Setting: East London. Participants: In 2001, white British (573) and Bangladeshi (682) school pupils from a representative sample of schools completed a self-report questionnaire that assessed their cultural, social and health characteristics. In 2003, 383 white British and 517 Bangladeshi pupils were resurveyed and completed measures of mental health. Main outcome measure: Strengths and difficulties questionnaire. Results: Bangladeshi pupils preferring clothes from their own cultural group (traditional clothing) were less likely to have later mental health problems when compared with Bangladeshi pupils showing an equal preference for clothing from their own and other cultures (integrated clothing; odds ratio (OR) 0.3, 95% CI 0.1 to 0.9). In gender-specific analyses, this finding was sustained only among Bangladeshi girls (OR 0.1, 95% CI 0.1 to 0.7). Integrated clothing choices were least risky only for white British adolescents. Friendship choices showed no prospective associations with later mental health problems. Conclusions: Cultural identity, expressed by clothing preferences, influences mental health; the effects differ by gender and ethnic group.